Cultural Artifacts Transform Embodied Practice: How a Sommelier Card Shapes the Behavior of Dyads Engaged in Wine Tasting - Rączaszek-Leonardi, Joanna; Krzesicka, Julia; Klamann, Natalia; Ziembowicz, Karolina; Denkiewicz, Michał; Kukiełka, Małgorzata; Zubek, Julian (Frontiers in Psychology, 2019)
The radical embodied approach to cognition directs researchers’ attention to skilled practice in a structured environment. This means that the structures present in the environment, including structured interactions with others and with artefacts, are put at least on a par with individual cognitive processes in explaining behaviour. Both ritualized interactive formats and artefacts can be seen as forms of “external memory”, usually shaped for a particular domain, that constrain skilled practice, perception and cognition in on-line behaviour and in learning and development. In this paper, we explore how a task involving the recognition of difficult sensory stimuli (wine) by collective systems (dyads) is modified by a domain-specific linguistic artefact (a sommelier card). We point to how using the card changes the way participants explore the stimuli individually, making it more consistent with culturally accrued sommelier know-how, as well as how it transforms the interaction between the participants, creating specific divisions of labour and novel relations. In our exploratory approach, we aim to integrate qualitative methods from anthropology and sociology with quantitative methods from psychology and the dynamical systems approach using both coded behavioural data and automatic movement analysis.